Pengembangan Aplikasi e-Commerce Penjualan Tanaman Anggrek isitaman.com menggunakan Restful API - Ediashta Revindra Amirussalam; Widhy Hayuhardhika Nugraha Putra; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
e-commerce can facilitate goods trading, especially for business to customer, but the widespread use of e-commerce also creates new security problems, therefore the use of payment gateways is inseparable from the development of e-commerce, this research was conducted to develop e-commerce that meets the business value proportion of PT. Javina. The research that was carried out resulted in the isitaman.com e-commerce that is developed using Restful API, Laravel as a framework, and Midtrans as a payment gateway. This development is also done using the Agile Scrum method as a software development cycle. Then at the end of the development, testing was done using Nielsen's Attributes of Usability to measure the usability level of isitaman.com with a result of 4.0875 for effectiveness. It is hoped that this research can contribute to future research related to Restful API and E-commerce